CONTRIBUTION DE L’ALPHABETISATION A L’ESPACEMENT DES NAISSANCES EN MILIEU RURAL AU BENIN: CAS DE LA COMMUNE DE DOGBO - AHODEKON, SESSOU COOVI CYRIAQUE (My University, 2015)
Alphabetization and adult education being recognized as a lever that cannot be neglected in developmental process, Republic of Benin like most of the countries in the world, has put in place since the years 1970’s many alphabetization and adult education programs. Those programs that have very precise contents are implemented with more or less adapted methods, but do not always respond to the needs of the target beneficiary groups. In Dogbo Administrative District, alphabetization has been for the women, a means of solving their problems as they now have access to information. Alphabetization courses have also brought changes in their habits. They apply on daily basis the information in health domain particulary. Nevertheless, the development of a community by the integration of more important number of practices based on writing, transform the way the member’sconceived their life. But those women areconsciousthat alphabetization constitutes for them an opportunity that they have to seize as for a change to occur in their life, a canal that lead to the new world. The programs of integrated alphabetization of planning family, infantile and the maternal health has contributed to the growth of economic security of those families, the household as well as the community.Alphabetization grave possibility to the women to reach higher level in education even if there is real need to make more emphasis on the planning family.
Keywords: Alphabetization; Birth; Planning family; Contraceptive Methods